The nicotinic acetylcholine receptor and its prokaryotic homologues: Structure, conformational transitions & allosteric modulation. (September 2015) - Cecchini, Marco; Changeux, Jean-Pierre
Abstract: Pentameric ligand-gated ion channels (pLGICs) play a central role in intercellular communications in the nervous system by converting the binding of a chemical messenger – a neurotransmitter – into an ion flux through the postsynaptic membrane. Here, we present an overview of the most recent advances on the signal transduction mechanism boosted by X-ray crystallography of both prokaryotic and eukaryotic homologues of the nicotinic acetylcholine receptor (nAChR) in conjunction with time-resolved analyses based on single-channel electrophysiology and Molecular Dynamics simulations. The available data consistently point to a global mechanism of gating that involves a large reorganization of the receptor mediated by two distinct quaternary transitions: a global twisting and a radial expansion/contraction of the extracellular domain. These transitions profoundly modify the organization of the interface between subunits, which host several sites for orthosteric and allosteric modulatory ligands. The same mechanism may thus mediate both positive and negative allosteric modulations of pLGICs ligand binding at topographically distinct sites. The emerging picture of signal transduction is expected to pave the way to new pharmacological strategies for the development of allosteric modulators of nAChR and pLGICs in general. This article is part of the Special Issue entitled 'The Nicotinic Acetylcholine Receptor: From Molecular Biology to Cognition'. Highlights: We review recent advances in the structure, transitions and modulation of pLGICs. Simulation studies of pLGICs have shed new light on the mechanism of gating. We propose a model of gating involving two distinct quaternary transitions. We show how these transitions are regulated by ligand binding events. We present a complete though speculative model of signal transduction by pLGICs.